Approach to Diagnosis and Treatment of Drug Allergy - Pandapotan, Roy Akur; Rengganis, Iris (Jurnal Penyakit Dalam Indonesia, 2017)
Drug allergy is a serious medical problem. Drug allergy can be defined as an adverse drug reaction involving immunological mechanism. However, it is not easy to decide whether an adverse drug reaction is an allergic reaction, and it requires a systematically diagnostic approach. Beside a thorough history taking and physical examination, there are general and specific laboratory examination to investigate drug allergy which can be done in vivo, in vitro, or biopsy. The management of drug allergy include the avoidance of the precipitating event, and specific methods to reduce the drug reaction which include threating through, dosing test, desensitization, and the administration of premedication for certain drugs.